Students attitudes towards the assessment based on the alphabets grading system - Al Hileh, Mohammad M.; AbuFoudeh, Basel Khamis Salem (Opción, 2019)
The aim of this study is to investigate the attitudes of the students of Middle East University in Jordan towards alphabets scoring plus/minus system via comparative qualitative research methods. The results showed that students’ attitudes were generally positive towards the letter grading system. They also showed statistically significant differences (α = 0.05) in the students’ attitudes towards the letter grading system attributed to the faculty, gender, and interaction between them. In conclusion, the students’ attitudes of scientific faculties towards the letter grading system were more positive than those in humanitarian faculties